A Compact High-Pass Filter Using Hybrid Microstrip/Nonuniform CPW with Dual-Mode Resonant Response - Hui Chen; Di Jiang; Ke-Song Chen; Hong-Fei Zhao (International Journal of Antennas and Propagation)
A novel and miniature high-pass filter (HPF) based on a hybrid-coupled microstrip/nonuniform coplanar waveguide (CPW) resonator is proposed in this article, in which the designed CPW has exhibited a wideband dual-mode characteristic within the desired high-pass frequency range. The implemented filter consists of the top microstrip coupled patches and the bottom modified nonuniformly short-circuited CPW resonator. Simulated results from the electromagnetic (EM) analysis software and measured results from a vector network analyzer (VNA) show a good agreement. A designed and fabricated prototype filter having a 3 dB cutoff frequency (fc) of 5.78 GHz has shown an ultrawide high-pass behavior, which exhibits the highest passband frequency exceeding 4.0fc under the minimum insertion loss (IL) 0.75 dB. The printed circuit board (PCB) area of the filter is approximately 0.062λg×0.093λg, where λg is the guided wavelength at fc.